The Influence of Electro-Conductive Compression Knits Wearing Conditions on Heating Characteristics - Md. Reazuddin Repon (MDPI AG, 2021)
Textile-based heaters have opened new opportunities for next-generation smart heating devices. This experiment presents electrically conductive textiles for heat generation in orthopaedic compression supports. The main goal was to investigate the influence of frequent washing and stretching on heat generation durability of constructed compression knitted structures. The silver coated polyamide yarns were used to knit a half-Milano rib structure containing elastomeric inlay-yarn. Dimensional stability of the knitted fabric and morphological changes of the silver coated electro-conductive yarns were investigated during every wash cycle. The results revealed that temperature becomes stable within two minutes for all investigated fabrics. The heat generation was found to be dependent on the stretching, mostly due to the changing surface area; and it should be considered during the development of heated compression knits. Washing negatively influences the heat-generating capacity on the fabric due to the surface damage caused by the mechanical and chemical interaction during washing. The higher number of silver-coated filaments in the electro-conductive yarn and the knitted structure, protecting the electro-conductive yarn from mechanical abrasion, may ensure higher durability of heating characteristics.